Daily vs. hourly simulation for estimating future flood peaks in mesoscale catchments - Marcus Beylich; Uwe Haberlandt; Frido Reinstorf (Hydrology Research, 2021)
Daily hydrological models are commonly used to study changes in flood peaks due to climate change. Although they often lead to an underestimation of absolute floods, it is assumed that future flood peaks in smaller mesoscale catchments are less underestimated when examining the relative change signal of floods. In this study, the applicability of this hypothesis is investigated by comparing the results of a daily hydrological model set, calibrated on runoff hydrographs, with an hourly model set calibrated on flood peak distributions. For analysis, a daily RCP8.5 climate model ensemble is disaggregated to hourly values and the runoff is simulated on a daily and hourly basis for six mesoscale catchments in Central Germany. Absolute floods and relative flood changes are compared between both model sets. The results show significant differences between the absolute floods of both model sets, in most cases caused by underestimations due to the daily modeling process. In contrast, the differences between the two model sets are not significant for the relative change signal of the floods, especially for higher return periods. To improve results in climate studies with coarse modeling time step, the use of relative change signal of floods instead of absolute values is recommended. HIGHLIGHTS Flood peak changes in mesoscale catchments simulated using daily/hourly modeling time steps by disaggregating a daily RCP8.5 climate model ensemble.; Future absolute flood values and relative flood change signals compared between daily/hourly model results with significance testing.; Results: underestimation of absolute flood values (daily); no significant differences for relative flood change signals between daily/hourly models.;